1986
DOI: 10.1007/bf02427086
|View full text |Cite
|
Sign up to set email alerts
|

Progression of subclinical polyneuropathy in young patients with Type 1 (insulin-dependent) diabetes: associations with glycaemic control and microangiopathy (microvascular complications)

Abstract: Summary. The progression of subclinical polyneuropathy over 2.5 years has been studied in a representative group of 75 young patients with Type I (insulin-dependent) diabetes (initial age 16-19years). The relationships between changes in nerve function, glycaemic control and concurrently developing microvascular complications (retinopathy, microproteinuria) were investigated. Deterioration of motor, sensory and autonomic nerve function, retinopathy and microproteinuria was related to poor glycaemic control. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
2
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 41 publications
(42 reference statements)
7
40
2
1
Order By: Relevance
“…Puberty impairs insulin action both in patients with type 1 diabetes and in healthy adolescents (8), and our findings are largely in accordance with the obser- vation that poor metabolic control is the most important prognostic factor for neuronal dysfunction both in adolescent (2,20) and adult patients (7,21). The peripheral and autonomic nerve fibers of pubertal and postpubertal patients with diabetes may be the most vulnerable to nerve demyelination and axonal damage caused by poor metabolic control induced by the pubertal hormonal changes (8) and presumably also by poor motivation for self-care during puberty.…”
Section: Table 3-h-reflex Latency Difference (Milliseconds) In the Tisupporting
confidence: 90%
“…Puberty impairs insulin action both in patients with type 1 diabetes and in healthy adolescents (8), and our findings are largely in accordance with the obser- vation that poor metabolic control is the most important prognostic factor for neuronal dysfunction both in adolescent (2,20) and adult patients (7,21). The peripheral and autonomic nerve fibers of pubertal and postpubertal patients with diabetes may be the most vulnerable to nerve demyelination and axonal damage caused by poor metabolic control induced by the pubertal hormonal changes (8) and presumably also by poor motivation for self-care during puberty.…”
Section: Table 3-h-reflex Latency Difference (Milliseconds) In the Tisupporting
confidence: 90%
“…Tightening control in early pregnancy inevitably increases the frequency of hypoglycaemia. Recent work with rats has shown that hypoglycaemia at a critical stage of development-namely, equivalent to days 32-40 in humans (18)(19)(20)(21)(22)(23)(24)(25)(26) days after ovulation)-can cause congenital abnormalities.1316 Hence the desirability of reducing blood glucose concentrations in early pregnancy has been questioned. 16 This paper reports the first 14 years' experience of our prepregnancy clinic, comparing results in women who attended the clinic with those in a group of women who did not.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Young et al 21 reported that the deterioration of motor, sensory, and autonomic nerve function over 2.5 years among 75 adolescents with T1D was related to poor glycemic control. In a small clinic-based crosssectional study of 79 children with T1D, Chen et al 22 found that both A1c and duration were significant predictors of reduced HRV as measured by HF power.…”
mentioning
confidence: 99%